Correlation of social support with work family conflict: a study on career women in Sumatera Barat, Indonesia - Syapitri, Denia; Afdal, Afdal; Nurfarhanah, Nurfarhanah; Hariko, Rezki (International Journal of Research in Counseling and Education, 2023)
This research is motivated by the increasing number of working women in West Sumatra, which reached 68.50-74.36% in 2022. The dual role as wife and parent can cause work-family conflict. Social support is a factor that affects work-family conflict. This study analyzes the relationship between social support and work-family conflict in career women. This study uses a quantitative approach with a correlational method. The participants in this study were 60 career women as professionals in West Sumatra. The research instruments used were social support scale and work-family conflict scale. The research data were collected online and then analyzed using partial-least squares structural equation modeling (PLS-SEM) technique. The results of this study indicate that there is no significant relationship between the two variables, namely social support and work family conflict. In addition, the simultaneous effect analysis shows that only 16.1% of the variance can be explained, while 83.9% of the causal factors remain unknown. Based on the results of the study, with the help of counselors, career women are expected to understand, overcome problems, and develop skills through various counseling services, such as information services, group guidance and counseling, and family counseling.